Transportation costs and urban sprawl in Canadian metropolitan areas. (December 2016) - Young, Mischa; Tanguay, Georges A.; Lachapelle, Ugo
Abstract: We conduct an econometric analysis of the potential impact of gasoline and parking prices on urban sprawl in ten Canadian metropolitan areas from 1996 to 2011. Two measures of urban sprawl related to density and proximity are used as dependent variables: the proportion of low-density housing and the median commute distance. We explain these measures by four main variables based on the natural evolution model: population growth, median household income, the cost of surrounding agricultural land, and transportation costs. We show that, ceteris paribus, higher parking and gasoline prices have contributed to reduce the extent of urban sprawl. On average, a 1% increase in gasoline prices has led to a decrease in low-density housing by 0.17% and to a 0.04% decrease in median commute distance. Furthermore, we show that a 1% increase in the price of off-street parking has led to a 0.12% decrease in low-density housing and to a 0.05% decrease in median commute distance. We argue that results for parking prices are relatively modest because much free parking is available.